Lethality of Three Phasmarhabditis spp. (P. hermaphrodita, P. californica, and P. papillosa) to Succinea Snails - Jacob Schurkman; Irma Tandingan De Ley; Adler R. Dillman (Agriculture, 2022)
Succinea snails are considered to be invasive and pestiferous gastropods to those in the floricultural industry. Their small size makes them difficult to locate within large plant shipments, and their presence on decorative plants can constitute for an entire shipment to be rejected for sale and distribution. Research performed on Succinea snails is limited, especially in terms of effective mitigation strategies. The nematode Phasmarhabditis hermaphrodita is a biological control agent used on pestiferous gastropods throughout some European nations. Here, three strains of Phasmarhabditis from the United States (P. hermaphrodita, P. californica, and P. papillosa) were assessed as biological control agents against Succinea snails in controlled laboratory conditions, along with the molluscicide Sluggo Plus® as a control. All species of Phasmarhabditis applied at 30 IJs/cm2 caused significant mortality compared to the non-treated control and treatment with Sluggo Plus®. P. californica caused 100% mortality 6 days after exposure, while P. hermaphrodita and P. papillosa caused the same mortality rate 7 days after exposure. The molluscicide was unable to cause significant mortality compared to the non-treated control. Additional research with US Phasmarhabditis strains, including their non-target effects and distribution may lead to their being a viable option for biological control against Succinea snails.